Enhanced nitrogen removal in mainstream deammonification systems at ambient temperature by novel modified carriers and differentiation of microbial community transformation. (December 2022) - Li, Yuqi; Liang, Hong; Yang, Wenbo; Cheng, Lang; Cao, Jiasuo; Wang, Peng; Gao, Dawen
Graphical abstract: Highlights: Two novel carriers were proposed for enhancing the mainstream deammonification. The system with ZTP carriers possessed highest NRR throughout the whole operation. A more balanced activity and enhanced electron transfer was achieved in ZTP system. The surface roughness and metal element content was improved in both novel carriers. Novel carriers support AnAOB substrate by DNRA and PD under nitrate accumulation. Abstract: Zeolite-modified polyurethane (ZP) carriers and zeolite/tourmaline-modified polyurethane (ZTP) carriers were proposed to enhance mainstream deammonification. The system with ZTP carriers was rapidly established in 28 days with a nitrogen removal rate (NRR) of 0.150 kg N·(m 3 ·d) −1 . Moreover, the facilitative effect of tourmaline was suggested by the highest humic acid peak intensity and more balanced potential activity. Besides, SEM-EDS analysis revealed carrier characteristic improvement was achieved in both novel carriers while maintaining an excellent spatial structure. Moreover, the microbial analysis suggested that both modified carriers support the substrate supply to anaerobic ammonium oxidizing bacteria (AnAOB) by enhancing dissimilatory nitrate reduction to ammonium and partial denitrification under nitrate accumulation conditions. Nevertheless, the ZTP system had a greater advantage over maintaining the original AnAOB ( Candidatus Jettenia ) and ammonium oxidizing bacteria ( Nitrosomonas ) abundance. Overall, this study provides ZTP carriers with great potential for facilitating the establishment of mainstream deammonification at full-scale WWTPs.